Karakterisasi Gelatin Hasil Ekstraksi dari Tulang Sapi Melalui Proses Perlakuan Basa NaOH - Sitepu, Lorena; Fatimah, Siti (Jurnal Kartika Kimia, 2022)
Gelatin is a soluble protein that acts as a gelling agent and is commonly used as an ingredient in both food and non-food production. Since bone is composed of collagen fibers, it can be used as a raw material for gelatin production. Beef bone is a waste product that is rarely used. Sodium hydroxide (NaOH) can be used as a processing ingredient in the production of type B gelatin because it can remove fats and oils. The purpose of this study was to investigate the effects of 2%, 3%, 4%, 5%, and 6%NaOH concentrations on the properties of bovine bone gelatin at 4 and 6 hours of extraction time. The observed properties were yield, water content, ash content, pH, viscosity, and microbial contamination. The results showed that the pretreatment condition with 6% NaOH and extraction for 6 hours affected the properties of the highest yield, water content dan microbial contamination have fulfilled the SNI. The conclusion of this study is that NaOH can be used in the production of bovine bone gelatin, and there are some advances in producing gelatin with excellent properties for food and non-food applications.